Analisis Pengaruh Label Halal Pada Produk Makanan Terhadap Keputusan Pembelian Konsumen Masyarakat Kota Medan - Al-Bara ,; Rahmayanti Nasution (Intiqad: Jurnal Agama dan Pendidikan Islam, 2018)
The purpose of this study was to find out the influence of halal labels on the purchasing decisions of consumers in the city of Medan. Halal label is a halal statement written on the packaging issued on the basis of halal inauguration that integrates on product packaging as a legal guarantee, that the guarantee in question is halal to be used and consumed by the public, in accordance with the provisions of Islamic Shari'a and legislation. So, the number of food products circulating in the city of Medan, which do not have a halal label. But even so, the product continued to circulate widely, even many bought the product. On this basis, researchers want to see how to influence halal labels on consumers' decisions to buy a food product in the city of Medan. Meanwhile, residents in the Medan city are almost in balance, between Muslims and non-Muslims this study uses a quantitative approach. Data analysis techniques used are simple linear regression analysis and Determination test. This study uses a sampling method by accidental sampling and purposive sampling, by way of sampling by chance (spontaneity), but the sample chosen is also based on certain considerations, namely non-Muslim communities and Muslim communites.